2009
DOI: 10.3171/2009.5.focus0938
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after language mapping for insular World Health Organization Grade II gliomas in the dominant hemisphere: experience with 24 patients

Abstract: Object Despite the report of recent experiences of insular surgery in the past decade, there has been no series specifically dedicated to studying functional outcome following resection of insular WHO Grade II gliomas involving the dominant hemisphere, in patients with no or only mild preoperative language deficit. In this article, the authors analyze the contribution of awake mapping for preservation of brain function, especially language, in a homogeneous series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 50 publications
3
89
0
10
Order By: Relevance
“…6,11,13 Furthermore, surgery can be accomplished with a median EOR of 80%-82% and minimal morbidity of long-term language (0.8%) and motor function (1.6%). 2,3,8,13,14 The significance of volumetric EOR on overall survival for patients with both low-and high-grade insular gliomas has been demonstrated in multiple previously published reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,11,13 Furthermore, surgery can be accomplished with a median EOR of 80%-82% and minimal morbidity of long-term language (0.8%) and motor function (1.6%). 2,3,8,13,14 The significance of volumetric EOR on overall survival for patients with both low-and high-grade insular gliomas has been demonstrated in multiple previously published reports.…”
Section: Discussionmentioning
confidence: 99%
“…Prior published reports suggest that aggressive resection of both low-and high-grade insular gliomas may be accomplished with an acceptable morbidity profile. 2,3,[7][8][9][10]13,14,17 Maximal extent of resection (EOR) predicts superior overall and progression-free survival as well as improved seizure control. 6,11,13 The majority of insular gliomas not only involve the insular lobe but can also infiltrate into portions of the frontal operculum and temporal lobe.…”
mentioning
confidence: 99%
“…The publication of Yaşargil's experience 53 with these tumors prompted neurosurgeons to revisit the surgical option. Since the publication of that work in 1992, 53 several studies have shown a positive impact of tumor resection on PFS and OS with acceptable surgical morbidity rates for both low-grade (WHO Grade I and II) 2,9,10,15,17,19,39,46,55 and high-grade (WHO Grade III and IV) tumors. 27,34,37,46,55 Despite the lack of Class I evidence, data from several recent studies suggest that EOR is one of the main prognostic factors in OS, PFS, and ma-lignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports describing surgery of the insula may be of use as references. 6,7,17,28,37 The transsylvian approach with wide opening of the fissure for observation of this location may be effective; however, the risk of vascular injury and pial destruction is not insignificant. Furthermore, the transsylvian approach is associated with high neurological morbidity in surgery for medial temporal tumors.…”
Section: Transsubcentral Gyral Approachmentioning
confidence: 99%